Protective effects of ascorbic acid, DL-alpha-tocopherol acetate, and sodium selenate on ethanol-induced gastric mucosal injury of rats - (:unkn) unknown (HUMANA PRESS INC, 2004)
In this study, the effect of ascorbic acid (vitamin C), DL-alpha-tocopherol acetate (vitamin E), and sodium selenate (selenium) on ethanol-induced gastric mucosal injury in rats was investigated morphologically and biochemically. The gastric mucosal injury was produced by administration of 1 mL of absolute ethanol to each rat. Animals received vitamin C (250 mg/kg), vitamin E (250 mg/kg), and selenium (0.5 mg/kg) for 3 d 1 h prior to the administration of absolute ethanol. In gastric mucosa of rats given ethanol according to control groups, neuronal nitric oxide expression decreased. This immunoreactivity was much lower in the group given ethanol+vitamin C+vitamin E+selenium than the control group and the ethanol-induced group. Scanning electron microscopic evaluation of the ethanol-induced group, when compared to control groups, revealed degenerative changes in gastric mucosa, whereas a good arrangement in surface topography of gastric mucosa in the group given ethanol + vitamin C+vitamin E + selenium was observed. In the group administered ethanol, a reduction of the stomach glutathione (GSH) and serum total protein levels and increases in serum sialic acid, triglycerides, and stomach lipid peroxidation (LPO) levels were observed. Vitamin C+vitamin E+Se administration to alcohol-treated rats significantly increased the serum total protein, triglyceride levels, and stomach GSH levels and significantly lowered the levels of serum sialic acid and stomach LPO compared to untreated alcohol-supplemented rats. As a result of these findings, we can say that the combination of vitamin C, vitamin E, and selenium has a protective effect on ethanol-induced gastric mucosal injury of rats.
Keywords: ethanol; gastric mucosa; ascorbic acid; alpha-tocopherol acetate; sodium selenate; rat; INDUCED OXIDATIVE STRESS; PALM VITAMIN-E; LIPID-PEROXIDATION; NITRIC-OXIDE; SIALIC-ACID; OXYGEN RADICALS; GUINEA-PIGS; IN-VIVO; ALCOHOL; SELENIUM